Rok 1956 w polskim więziennictwie – realny przełom czy pozory totalitarnej odwilży? - Kwieciński, Adam (Wydawnictwo Uniwersytetu Wrocławskiego, 2023)
The Polish prison system in the first years after the end of World War II was considered part of the criminal apparatus of the security organs of the People’s Republic of Poland. Documented cases of drastic violations of the rights of convicts, the detention of political prisoners, torture, and inhumane conditions of confinement caused penitentiary units at the time to become deservedly infamous. The political thaw that began in October 1956 and the transition of the penitentiary system to the Ministry of Justice created an opportunity to restore the rule of law in penitentiaries and create humane conditions of imprisonment. This publication puts forward the thesis that the reforms undertaken by the new departmental authorities in the first decade since the transition of prisons to the jurisdiction of the Minister of Justice were in line with the spirit of modern penitentiary thought and the standards for prisoners’ rights adopted by the international community. Areas where these changes were most progressive and were given the greatest momentum were identified. The practice, to the extent necessary, was also reconstructed. It was also pointed out that already at the threshold of the reform undertaken, the limits and barriers to the initiated changes were clearly outlined. Their source was mainly the political context, but also the financial and material limitations of the Polish state. A not insignificant obstacle was also the change in the mentality of the staff of penitentiary units. The paper uses the method of historical-legal and dogmatic research.
Keywords: więziennictwo; kara pozbawienia wolności; skazany; praworządność; zakład karny